Carbon xerogel based electric double layer capacitors with polymer gel electrolytes – Improving the performance by adjusting the type of electrolyte and its processing. (10th July 2018) - Anneser, Katrin; Reichstein, Jakob; Braxmeier, Stephan; Reichenauer, Gudrun
Abstract: Polymer gel electrolytes for electric double layer capacitors (EDLC), also known as supercapacitors, represent a safe and low-cost alternative to liquid electrolytes. This study shows that EDLCs with polymer gel electrolytes may accomplish gravimetric capacitances comparable to or even higher than those of EDLCs with the same carbon electrodes and the respective ions in aqueous electrolyte. One of the most important parameters in this context is the effective electrode/electrolyte interface. This can be improved by using a suitable electrode and assembling method for the polymer electrolyte component. As polymer gel electrolytes we investigated polyvinyl alcohol (PVA) with either phosphoric or sulfuric acid as well as PVA and sulfuric acid with hydroxyethyl-cellulose as an additive in combination with porous carbon (xerogel) electrodes with different meso/macrostructures. The gravimetric capacitances determined for EDLCs with the sulfuric PVA electrolyte were considerable higher than those of EDLCs using phosphoric acid. Furthermore, the results of our study indicate a clear influence of the electrodes pore structure and the applied assembling method on the specific capacitance. The processing method providing the best contact between polymer electrolyte and electrode yields EDLCs with a gravimetric capacitance comparable to or even higher than that of EDLCs with liquid H2 SO4 . The experimental findings strongly suggest that micropores in the interconnected carbon backbone of the electrode - including such in regions that are not in direct contact with the polymer gel phase - are saturated with electrolyte and contribute to the capacitance. Graphical abstract: Image 1